PEMBERIAN SANKSI BAGI APARATUR SIPIL NEGARA YANG MELAKUKAN PELANGGARAN DISIPLIN BERAT - Afrita Miranti; Yogo Pamungkas (Reformasi Hukum Trisakti, 2021)
This was experienced by Sri Endang Mulyani, who was subjected to severe disciplinary punishment with the object of dispute in the form of a Decree of the Governor of Central Java on suspicion of having a special relationship with a man who was not her legal husband. The main problem discussed in this thesis is whether the actions committed by Sri Endang Mulyani in Decision Number 20/G/2020/PTUN.SMG can be said to be serious disciplinary violations and whether the process of examining and imposing sanctions given by the Governor of Central Java is in accordance with Government Regulation Number 53 of 2010. To answer this problem a research was carried out, with the nature of descriptive analysis research, and the results of the research were carried out qualitatively and conclusions were made using the deductive method, which resulted in the conclusion that the violations committed by Sri Endang Mulyani could not be said to be a serious disciplinary violation and the inspection process carried out by the Governor of Central Java was appropriate, but the imposition of sanctions by the Governor of Central Java was not in accordance with Government Regulation Number 53 of 2010.